The Effect of the Cool Intense Pulsed Light (CIPL) on Hair Removal of Chin Area in Hirsute Women - SH Njafei Dolatabadi; N Tabatabaei; F Hossein Zadh; R Mohammadi; A Afrasiabifar (Armaghane Danesh Bimonthly Journal, 2012)
Abstract